Identifying of rotor converter effects on the chopper control slip ring induction motor performances under grid voltage unbalance - Ameen, Hilmi Fadhil; Rasool, Ali Abdulqadir (Eastern-European Journal of Enterprise Technologies, 2025)
A lot of major industrial applications use three-phase Wound Rotor Induction Motor Drive Systems (WRIMDS), particularly in cement mills because of their performance control capabilities. When a power supply is subjected to the unbalanced voltages, the motor performance is affected. The object of the study is the Wound Rotor Induction Motor Drive Systems under unbalanced supply voltage. The subject of this research is the effect of harmonics under unbalanced supply conditions on the rotor circuit of WRIM with the presence of rectifiers and the chopper circuit. The investigation assesses the stator current, the rotor current, and electromagnetic torque components using a mathematical equivalent circuit representation. The analysis of this study presents the way for predicting the whole harmonic frequencies that belong to the currents of the stator, the rotor current, and the electromagnetic torque in terms of supply frequency and the rotor slip. The simulation and the proposed mathematical model results have shown good accuracy. The results show that the performance of WRIM, the variation of the motor currents, and the torque pulsation are dependent on the magnitude of the voltage unbalance factor and the duty cycle of the chopper circuit. The results of this study demonstrate that the unbalanced supply voltage has a negative impact on the increase of stator harmonic currents injected from the rotor side, rotor harmonic currents, and torque pulsation; as a result, the performance of WRIMDS has been derated. It is noticed from the results that the obtained currents are accurate, excluding the currents at a slip of one sixth in which a noteworthy variance is observed. The speed ripple is increased by 0.38 %, and torque ripple by 16.6 % when the voltage supply unbalance factor varies from (0 to 10) %